Analyzing the role of citizen science in modern research - Ceccaroni, Luigi, 1969-; Piera, Jaume, 1966- (Advances in knowledge acquisition, transfer, and management (AKATM) book series, 2017)
"This book focuses on analyzing data on current initiatives and best practices in citizen engagement and education programs across various disciplines by highlighting emergent research and application techniques within citizen science initiatives"--Resumé vydavatele